2006
DOI: 10.1152/ajpgi.00318.2005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of tumor necrosis factor-α modulation of intestinal epithelial tight junction barrier

Abstract: A TNF-alpha-induced increase in intestinal epithelial tight junction (TJ) permeability has been proposed to be an important proinflammatory mechanism contributing to intestinal inflammation in Crohn's disease and other inflammatory conditions. Previous studies from our laboratory suggested that the TNF-alpha-induced increase in intestinal TJ permeability was mediated by an increase in myosin light chain kinase (MLCK) protein expression. However, the molecular mechanisms that mediate the TNF-alpha increase in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
264
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 344 publications
(276 citation statements)
references
References 40 publications
10
264
2
Order By: Relevance
“…In the presence of hr IL-6 and hr MCP-1, the expression of ZO-1 proteins was downregulated in D407 cells (Figures 5d and e), thereby impairing HRPE monolayer integrity (Figure 5c). TNF-a is often associated with viral infection and has been reported to impair the intestinal epithelial tight junction barrier; 45 however, in D407 cells we could not detect the release of TNF-a, possibly because different epithelial cells show distinct properties in response to viral infection. In addition, IL-6 and MCP-1 exerted no effect on the expressions of Occludin, Claudin-1, Claudin-2, Claudin-3, Claudin-4, or Claudin-5.…”
Section: Discussioncontrasting
confidence: 64%
“…In the presence of hr IL-6 and hr MCP-1, the expression of ZO-1 proteins was downregulated in D407 cells (Figures 5d and e), thereby impairing HRPE monolayer integrity (Figure 5c). TNF-a is often associated with viral infection and has been reported to impair the intestinal epithelial tight junction barrier; 45 however, in D407 cells we could not detect the release of TNF-a, possibly because different epithelial cells show distinct properties in response to viral infection. In addition, IL-6 and MCP-1 exerted no effect on the expressions of Occludin, Claudin-1, Claudin-2, Claudin-3, Claudin-4, or Claudin-5.…”
Section: Discussioncontrasting
confidence: 64%
“…Although Ma et al (11) also reported that TNF could induce increases in Caco-2 MLCK expression, they found that this up-regulation was blocked by NFB inhibition. Ma et al recently reported that the a single NFB binding site mediates a 50% increase in transcription in response to TNF (43). We have located this site ϳ150bp upstream of exon 1A, downstream of the 3Ј Sp1 site.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, thiamin deficiency elevated the mRNA level of MLCK may be partly due to the upregulation of pro-inflammatory cytokines mRNA levels. Studies had been shown that TNF-a [55] and IL-1b [56] can up-regulate the expression of MLCK in human Caco-2 cells. According to our results, correlation analysis revealed that the mRNA levels of MLCK were positively correlated with IFN-g2, TNF-a, IL-1b and IL-8 mRNA levels in young grass carp intestine, suggesting that dietary thiamin deficiency led to elevate the mRNA level of MLCK may be partly related to the up-regulated pro-inflammatory cytokines mRNA levels in fish.…”
Section: Discussionmentioning
confidence: 99%